KESULITAN DALAM PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR: ANALISIS PENYEBAB DAN STRATEGI MENGATASINYA - Muhammad Arif Priatna; Ajeng Hikmalia Dwi Putri, Lulu Nur Anisha, Nurfitria (CV. ADIBA ASIHA AMIRA, 2025)
In primary schools in Indonesia, learning Indonesian often faces various problems, both from students and the teaching system. Based on relevant journal sources, this article aims to analyse the problems faced by students in learning Indonesian in primary schools and their solutions. The method used is a literature study or research on the factors that influence learning Indonesian in primary school and their solutions. The results of the analysis from various journals show that some of the factors that cause difficulties in learning Indonesian include difficulties in reading and writing, lack of vocabulary, low concentration in learning, and boredom in students. Each of these factors is interrelated and can hinder the development of students' language skills. To overcome these problems, teachers can apply various strategies, such as getting students used to reading every day, training writing habits in various appropriate ways, creating an environment conducive to improving concentration, and overcoming students' boredom with varied learning methods.